2017
DOI: 10.1103/physrevlett.119.195001
|View full text |Cite
|
Sign up to set email alerts
|

Electron Shock Ignition of Inertial Fusion Targets

Abstract: It is shown that inertial confinement fusion targets designed with low implosion velocities can be shock-ignited using laser-plasma interaction generated hot electrons (hot-e's) to obtain high energy gains. These designs are robust to multimode asymmetries and are predicted to ignite even for significantly distorted implosions. Electron shock ignition requires tens of kilojoules of hot-e's which can be produced only at a large laser facility like the National Ignition Facility, with the laser-to-hot-e conversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…The same remains true for the so-called alternative ignition schemes such as fast ignition, either with electrons or protons, or shock ignition. The first phase of any alternate ignition scheme always requires capsule compression to high areal densities to achieve the stopping power of fast charged particles, or electron assisted shock [48]. Notwithstanding that other detrimental effects such as laser parametric instabilities and energy coupling [49] are also at play in the performance degradation of ICF implosions, hydrodynamic instabilities and mix play a central role.…”
Section: Hydrodynamics Instabilities In Inertial Confinement Fusionmentioning
confidence: 99%
“…The same remains true for the so-called alternative ignition schemes such as fast ignition, either with electrons or protons, or shock ignition. The first phase of any alternate ignition scheme always requires capsule compression to high areal densities to achieve the stopping power of fast charged particles, or electron assisted shock [48]. Notwithstanding that other detrimental effects such as laser parametric instabilities and energy coupling [49] are also at play in the performance degradation of ICF implosions, hydrodynamic instabilities and mix play a central role.…”
Section: Hydrodynamics Instabilities In Inertial Confinement Fusionmentioning
confidence: 99%
“…Multiple shock reflections off the incoming inner shell and an increase in gas pressure cause the deceleration phase to begin. During the deceleration phase, the compressing material enclosed by the inner shell surface develops into a lowdensity, high-temperature region called the "hot spot" [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Those hot electrons with energy below 100 keV can significantly boost the shock pressure [13]. Recently Shang et al showed for laser-hot electron conversion efficiency of η > 10%, ignition can be achieved with 400 kJ compression and 100 kJ ignition pulse energy in what they call electron shock ignition [14]. Measuring and understanding LPI and hot electron generation in SI is critical [15][16][17][18][19][20][21][22][23].…”
mentioning
confidence: 99%
“…PIC simulations with the experimental conditions and the laser incident from plasma density n e = 0.12n c yielded η = 12% [25], where n c is the critical density of the incident laser. This motivated ignition-scale electron shock ignition design in [14] with the expectation that η would increase in longer scale lengths and stronger SRS. The PIC simulations in [14] with L n = 314 µm and laser incident from n e = 0.2n c did show an η = 25%.…”
mentioning
confidence: 99%
See 1 more Smart Citation